IMPLEMENTASI PEMERINTAHAN YANG BERSIH DALAM KERANGKA RENCANA AKSI DAERAH PEMBERANTASAN KORUPSI (RAD-PK) (Studi Di Kabupaten Pemalang) - Muhammad Fauzan; Bahtaruddin Bahtaruddin; Hikmah Nuraini (Faculty of Law, Universitas Jenderal Soedirman, 2012)
This research related to the implementation of good governance, free from corruption, collusion and nepotism. The approach used in this research is a descriptive qualitative approach. The Location of research conducted in the District of Pemalang. Based on the research results can presented that the District of Pemalang is committed and fully supports the government policy in eradicating corruption. District of Pemalang support to efforts to more information accelerate the eradication of corruption stated in the the Regional Action Plan to Accelerate the Eradication of Corruption (RAD-PK) in 2011 -2016 which refers to the Medium Term Development Plan (RPJM) District of Pemalang from 2011 to 2016 and the National Action Plan for Eradication of Corruption (RAN-PK) and the President of Republic of Indonesia Instruction No. 5 Year 2004 on Accelerating the eradication of corruption. RAD-PK 2011-2016 District of Pemalang is a document that contains an action program that aims to accelerate the eradication of corruption. RAD-PK as a program of action containing concrete measures that have been agreed by the stakeholders in the area, so it has been a commitment of local governments prevention efforts corruption through the development of programs and activities aimed at improving public services and the application of the principles of good governance. Keywords: governance, eradication, corruption